Hemostatic powder spray: a new method for managing gastrointestinal bleeding. (May 2015) - Changela, Kinesh; Papafragkakis, Haris; Ofori, Emmanuel; Ona, Mel A.; Krishnaiah, Mahesh; Duddempudi, Sushil; Anand, Sury
Gastrointestinal bleeding is a leading cause of morbidity and mortality in the United States. The management of gastrointestinal bleeding is often challenging, depending on its location and severity. To date, widely accepted hemostatic treatment options include injection of epinephrine and tissue adhesives such as cyanoacrylate, ablative therapy with contact modalities such as thermal coagulation with heater probe and bipolar hemostatic forceps, noncontact modalities such as photodynamic therapy and argon plasma coagulation, and mechanical hemostasis with band ligation, endoscopic hemoclips, and over-the-scope clips. These approaches, albeit effective in achieving hemostasis, are associated with a 5–10% rebleeding risk. New simple, effective, universal, and safe methods are needed to address some of the challenges posed by the current endoscopic hemostatic techniques. The use of a novel hemostatic powder spray appears to be effective and safe in controlling upper and lower gastrointestinal bleeding. Although initial reports of hemostatic powder spray as an innovative approach to manage gastrointestinal bleeding are promising, further studies are needed to support and confirm its efficacy and safety. The aim of this study was to evaluate the technical feasibility, clinical efficacy, and safety of hemostatic powder spray (Hemospray, Cook Medical, Winston-Salem, North Carolina, USA) as a new method for managing gastrointestinal bleeding. In this review article, we performed an extensive literature search summarizing case reports and case series of Hemospray for the management of gastrointestinal bleeding. Indications, features, technique, deployment, success rate, complications, and limitations are discussed. The combined technical and clinical success rate of Hemospray was 88.5% (207/234) among the human subjects and 81.8% (9/11) among the porcine models studied. Rebleeding occurred within 72 hours post-treatment in 38 patients (38/234; 16.2%) and in three porcine models (3/11; 27.3%). No procedure-related adverse events were associated with the use of Hemospray. Hemospray appears to be a safe and effective approach in the management of gastrointestinal bleeding.